ОСОБЕННОСТИ РАЗРАБОТКИ СИСТЕМЫ ЭКОЛОГИЧЕСКОГО МЕНЕДЖМЕНТА ДЛЯ РЕКРЕАЦИОННЫХ ТЕРРИТОРИЙ (Географический вестник=Geographical bulletin, 2017)
В статье приведены концептуальные особенности разработки системы экологического менеджмента. Выявлены основные закономерности создания экологического менеджмента для туристско- рекреационных территорий.THE PECULIARITIES OF WORKING OUT OF THE SYSTEM OF ECOLOGICAL MANAGEMENT FOR RECREATION TERRITORYIn the article there are the peculiarities of working out of the system of ecological management. The main reasons of working out of ecological management for tourist-recreation zone. The system of ecological management is elaborated on the example of Ust-Kachka resort-recreation zone.